Rapid purification of serine proteinases from Bothrops alternatus and Bothrops moojeni venoms - Fernandes de Oliveira, Liliane Maria [UNESP]; Ullah, Anwar [UNESP]; Masood, Rehana [UNESP]; Zelanis, Andre; Spencer, Patrick J.; Serrano, Solange M. T.; Arni, Raghuvir K. [UNESP] (Elsevier B.V., 2013)
Envenomation by Bothrops species results, among other symptoms, in hemostatic disturbances. These changes can be ascribed to the presence of enzymes, primarily serine proteinases some of which are structurally similar to thrombin and specifically cleave fibrinogen releasing fibrinopeptides. A rapid, three-step, chromatographic procedure was developed to routinely purify serine proteinases from the venoms of Bothrops alternatus and Bothrops moojeni. The serine proteinase from B. alternatus displays an apparent molecular mass of similar to 32 kDa whereas the two closely related serine proteinases from B. moojeni display apparent molecular masses of similar to 32 kDa and similar to 35 kDa in SDS-PAGE gels. The partial sequences indicated that these enzymes share high identity with serine proteinases from the venoms of other Bothrops species. These proteins coagulate plasma and possess fibrinogenolytic activity but lack fibrinolytic activity. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Serine proteinase; Crude venom; Bothrops alternatus; Bothrops moojeni; Fibrinogenolysis; Proteolytic activity